First report of hyperphosphatemic familial tumoral calcinosis due to homozygous GALNT3 mutation in a 16-year-old boy - Shukla, Ajay; Gupta, Sushil; Tignath, Gargi (International Journal of Research in Medical Sciences, 2025)
Hyperphosphatemic familial tumoral calcinosis (HFTC) is a rare disorder HFTC is caused by a loss of function in fibroblast growth factor 23 (FGF23), leading to increased phosphate levels in the body and calcium deposition. It also has an autosomal trait with presentation early in childhood or 2nd decade of life. Mutation of polypeptide N-acetylgalactosaminyltransferase 3 (GALNT3) and Klotho (KL) gene are seen in HFTC. We present the first reported case of a 16-year-old boy diagnosed witsh HFTC due to a homozygous GALNT3 gene mutation at exon 5 (Leu366Arg). The patient exhibited calcinosis in the left gluteal region and hyperphosphatemia. Surgical excision and genetic analysis confirmed the diagnosis. Our aim is to highlight the role of genetic screening in HFTC diagnosis and explore novel mutations, advancing research in rare metabolic disorders.